EFL Obstacles in Writing Thesis Proposal - Prasetyaningrum, Ari; Wati, Laila; Ayu Surayya, Siti; Asrobi, Maman (LPPM Universitas Pancasakti Tegal, 2021)
This study aimed to analyze the students’ obstacles when writing a thesis proposal. Subjects of this study were 20 learners in the English Language Education Study Program at Hamzanwadi University in the academic year 2020-2021. The data were collected by using a questionnaire with 27 items to obtain students’ opinions about their problems in writing a thesis proposal. A descriptive quantitative design was used in this research. Having revealed the research analysis, it was found that the participants experienced four types of obstacles: 1) describing data analysis (40 %), 2) finding relevant references (60 %), 3) lack of vocabulary (50 %), and 4) writing theoretical and framework (45 %). To solve the learners’ problems in accomplishing the thesis proposal, there are some suggestions. Students should learn more about grammar and practice how to arrange qualified thesis and read various books to get new vocabulary. The advisors should give a detailed and specific explanation to make sure the students understand the explanation.